The effects of male proximity, apparent size, and absolute size on female preference in the sailfin molly, Poecilia latipinna - MacLaren, R. David (Behaviour, 2006)
Female sailfin mollies (Poecilia latipinna) prefer males of greater lateral projection area. This preference may reflect perceptual constraints on the female. A larger male may project a larger image onto the female's retina at a given viewing distance. This may elicit greater stimulation of the visual system and thus a stronger behavioral response. This study investigates the effects of male proximity, apparent size, and absolute size on female preference in sailfin mollies. I examine whether females base their mate preferences on the male's actual size, or on the size of the image he projects on the female's retina (apparent size). The question of actual vs apparent size preferences in fish has been addressed within the context of optimal prey-size selection, but this study is believed to be the first to examine the question in the context of sexual selection. I presented females with pairs of dummy males in seven treatments organized into four categories: (1) The Actual Size Control - a single treatment where male actual size was held constant while varying female viewing distance; (2) The Distance Controls - three treatments in which male distance from the female subject was held constant, while varying actual size; (3) The Apparent Size Controls - two treatments where both body size and viewing distances varied, while holding apparent size constant; and (4) The Experimental treatment - a single test in which the smaller male of the pair appeared larger. In each of the Actual Size and Distance Control treatments, females preferred the closer and larger males, respectively. However, females exhibited no preferences in either of the Apparent Size Control treatments. Additionally, females in the Experimental treatment preferred the apparently larger dummy to the male that was actually larger. These results suggest that female preference for male size is based on the male's apparent size - i.e., that preference is based on the size of the image projected on the female's retina, rather than the male's actual body size. The evolutionary implications of these results with regard to courtship strategies and male secondary sex traits are discussed.